Transcriptional inhibition of STAT1 functions in the nucleus alleviates Th1 and Th17 cell-mediated inflammatory diseases - Park, Jiyoon; Son, Min-Ji; Ho, Chun-Chang; Lee, Su-Hyeon; Kim, Yuna; An, Jaekyeung; Lee, Sang-Kyou (Frontiers in Immunology, 2022)
T helper 1 cells (Th1 cells) and T helper 17 cells (Th17 cells) play pivotal roles in the pathogenesis of various autoimmune diseases, including psoriasis and inflammatory bowel disease (IBD). Signal transducer and activator of transcription 1 (STAT1) regulates the Th1 and Th17 cell lineage commitment at an early stage and maintains their immunological functions in vitro and in vivo. The previous strategies to block STAT1 functions to treat autoimmune diseases inhibit Th1 cell activity but simultaneously cause hyper-activation of Th17 cells. Herein, to modulate the functions of pathogenic Th1 and Th17 cells without genetic modification in normal physiological conditions, we generated the nucleus-deliverable form of the transcription modulation domain of STAT1 (ndSTAT1-TMD), which can be transduced into the nucleus of the target cells in a dose- and time-dependent manner without affecting the cell viability and T cell activation signaling events. ndSTAT1-TMD significantly blocked the differentiation of naïve CD4+ T cells into Th1 or Th17 cells via competitive inhibition of endogenous STAT1-mediated transcription, which did not influence Th2 and Treg cell differentiation. When the gene expression profile of Th1 or Th17 cells after ndSTAT1-TMD treatment was analyzed by mRNA sequencing, the expression of the genes involved in the differentiation capacity and the immunological functions of Th1 or Th17 cells were substantially reduced. The therapeutic potential of ndSTAT1-TMD was tested in the animal model of psoriasis and colitis, whose pathogenesis is mainly contributed by Th1 or/and Th17 cells. The symptoms and progression of psoriasis and colitis were significantly alleviated by ndSTAT1-TMD treatment, comparable to anti-IL-17A antibody treatment. In conclusion, our study demonstrates that ndSTAT1-TMD can be a new therapeutic reagent for Th1/17 cell-mediated autoimmune diseases by modulating the functions of pathogenic Th1 and Th17 cells together.